Development of visual thinking strategy in augmented reality (ViTSAR) to facilitate visual literacy skills on magnetic field material - Yudi Guntara; Asep Saefullah; Yayat Ruhiat; Alifya Nabila Subaedi (Universitas Sultan Ageng Tirtayasa, 2023)
Students poorly understand the magnetic field material concept due to difficulties visualizing it. So, it takes a skill that can support the ability to visualize magnetic field material to practice these skills requires the right strategy and learning media. Therefore, this study aims to develop and determine the feasibility and response of students to the acceptance of Visual Thinking Strategy in Augmented Reality (ViTSAR) learning media technology to facilitate visual literacy skills on magnetic field material. The research method used is Research and Development (R& D) with a 4-D development model (Define, Design, Develop, and Disseminate). Through due diligence conducted by material experts, the average value of all aspects was 6.7 with feasible criteria, and media experts obtained an average value of 6.81 with feasible criteria. In contrast, the trial was limited to 15 3rd-semester students of Physics Education at Sultan Ageng Tirtayasa University, who responded well to technology acceptance with an overall average assessment result of 6.36. These results show that ViTSAR learning media on magnetic field material can be used as a learning supplement in introductory Physics II lectures on magnetic field material.